Primary biliary cirrhosis–autoimmune hepatitis overlap syndrome in a patient with paroxysmal nocturnal hemoglobinuria: a case report. Issue 5 (May 2021) - Chen, Lin; Shi, Xiaodong; Jin, Jinglan; Han, Wei; Qu, Limei; Li, Wanyu
Primary biliary cirrhosis (PBC)–autoimmune hepatitis (AIH) overlap syndrome is frequently associated with extrahepatic autoimmune disorders. Paroxysmal nocturnal hemoglobinuria (PNH) is an acquired disease that is characterized by complement-mediated hemolysis due to erythrocyte membrane defects. However, autoimmune liver disease was not previously reported to be associated with PNH. A 37-year-old female patient was referred to our hospital with elevated liver enzymes and hematuria. On the basis of the symptoms and results of laboratory tests, radiographic studies, and pathologic results, she was diagnosed with PBC–AIH overlap syndrome and PNH. She was treated with a combination of ursodeoxycholic acid and prednisolone. The patient was symptom-free, with laboratory findings within near-normal range. The patient had recovered well at the 24-month follow-up evaluation. While we acknowledge that this was a single case, these findings expand our knowledge of immunological diseases that are associated with PNH and suggest an immune-mediated pathogenic pathway between PNH and PBC–AIH overlap syndrome. The combination of ursodeoxycholic acid and prednisolone can achieve therapeutic success. Routine follow-up of these patients is necessary to document disease progression.